Raising Healthy Children: Packing a Peanut-Free Lunch - Sarah Schmidt; Karla Shelnutt; Gail Kauwell (EDIS)
Peanut butter is a staple in the diets of many children, but it can cause serious problems for those with a peanut allergy. Knowing how to identify foods that contain peanuts, what to pack for school lunches, and how to reduce accidental contact with peanuts will help keep children with peanut allergies safe when they are away from home. This 5-page fact sheet was written by Sarah Schmidt, Karla Shelnutt, and Gail Kauwell, and published by the UF Department of Family Youth and Community Sciences, February 2013.